Study on the Impact of Digital Economy Enabling High-Quality Economic Development in Yunnan Province - Wang, Hao; Wen, Chunyan (International Journal of Global Economics and Management, 2024)
This article aims to explore the role of digital economy and its mechanism in promoting the high-quality development of Yunnan Province's economy. By constructing an evaluation index system and applying econometric methods, the current situation of the digital economy in Yunnan Province and its impact on the high-quality development of the economy are comprehensively analyzed. It is found that the digital economy has a significant positive contribution to the high-quality development of Yunnan Province's economy, and indirectly affects the high-quality development of the economy by enhancing the level of entrepreneurship. In addition, there is a non-linear relationship between the digital economy and high-quality economic development, and the promotion effect of the digital economy on high-quality economic development varies significantly across different levels of economic development. Based on these findings, the article puts forward policy recommendations such as comprehensively promoting the development of the digital economy and implementing a differentiated digital economy development strategy in order to promote the sustainable development of Yunnan Province and the wider region in the era of the digital economy.